SISTEM INFORMASI PONDOK PESANTREN NURUL IMAN MUARO JAMBI BERBASIS WEB: INFORMATION SYSTEM, PONDOK PESANTREN NURUL IMAN, MUARO JAMBI - Purnama, Fery (LP2M STMIK Nurdin Hamzah Jambi, 2018)
Pondok Pesantren Nurul Iman Muaro Jambi is one of foundation that is in kabupaten muaro jambi .Information media are dipondok pesantren still still not use internet media , to follow time progress the complex this and introduce pondok pesantren nurul iman virtual world , it takes information systems and are equipped with the registration form santri online , and produce information that more update .The purpose of the construction these information systems is meant to make ease the registration process santri also attends located outside regions .Because santri pondok pesantren nurul iman not only come from kabupaten muaro jambi just , namely tanjung jabung east , tanjung jabung west , bahakan from outside provincial as palembang , riau , lampung .Excess of these information systems assist the pondok pesantren in dataWith dirancangnya information system is expected to optimize the candidates santri to the registration online .That the process the registration was not manually again.